Magnetic Resonance Imaging or Computed Tomography Before Treatment in Acute Ischemic Stroke: Effect on Workflow and Functional Outcome. Issue 3 (March 2019) - Provost, Corentin; Soudant, Marc; Legrand, Laurence; Ben Hassen, Wagih; Xie, Yu; Soize, Sébastien; Bourcier, Romain; Benzakoun, Joseph; Edjlali, Myriam; Boulouis, Grégoire; Raoult, Hélène; Guillemin, Francis; et al.
Abstract : Background and Purpose—: The acute management of stroke patients requires a fast and efficient screening imaging modality. We compared workflow and functional outcome in acute ischemic stroke patients screened by magnetic resonance imaging (MRI) or computed tomography (CT) before treatment in the THRACE trial (Thrombectomie des Artères Cérébrales), with the emphasis on the duration of the imaging step. Methods—: The THRACE randomized trial (June 2010 to February 2015) evaluated the efficacy of mechanical thrombectomy after intravenous tPA (tissue-type plasminogen activator) in ischemic stroke patients with proximal occlusion. The choice of screening imaging modality was left to each enrolling center. Differences between MRI and CT groups were assessed using univariable analysis and the impact of imaging modality on favorable 3-month functional outcome (modified Rankin Scale score of ⩽2) was tested using multivariable logistic regression. Results—: Four hundred one patients were included (25 centers), comprising 299 MRI-selected and 102 CT-selected patients. Median baseline National Institutes of Health Stroke Scale score was 18 in both groups. MRI scan duration (median [interquartile range]) was longer than CT (MRI: 13 minutes [10–16]; CT: 9 minutes [7–12]; P <0.001). Stroke-onset-to-imaging time (MRI: median 114 minutes [interquartile range, 89–138]; CT: 107 minutes [88–139]; P =0.19), onset-to-intravenous tPA time (MRI: 150 minutes [124–179]; CT: 150 minutes [123–180]; P =0.38) and onset-to-angiography-suite time (MRI: 200 minutes [170–250]; CT: 213 minutes [180–246]; P =0.57) did not differ between groups. Imaging modality was not significantly associated with functional outcome in the multivariable analysis. Conclusions—: Although MRI scan duration is slightly longer than CT, MRI-based selection for acute ischemic stroke patients is accomplished within a timeframe similar to CT-based selection, without delaying treatment or impacting functional outcome. This should help to promote wider use of MRI, which has inherent imaging advantages over CT. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01062698. Abstract : Supplemental Digital Content is available in the text.